Feasibility of Imaging Esophageal Cancer with Labeled Somatostatin Analogue. (21st February 2011) - Herlin, Gunnar; Ideström, Lars; Lundell, Lars; Aspelin, Peter; Axelsson, Rimma
Abstract : Background . While the surface of a cell normally has some amount of somatostatin receptors, these receptors are overexpressed to a very high degree in multiple neoplastic diseases. No data exist for esophageal carcinoma. Purpose . To find out whether esophageal carcinoma could be imaged using somatostatin receptor scintigraphy. Material and Methods . 34 patients with esophageal lesions were prospectively examined by 99m Tc-depreotide scintigraphy 2 and 4 hours after injection. Quantitative evaluation of 99m Tc-depreotide uptake was performed around the lesion ( T ) and in healthy lung parenchyma ( B ). The relative uptake was calculated as T−B/B . Scintigraphy results were compared with histopathology from surgery or biopsy specimens from endoscopic ultrasonography. Results . 21 patients had esophageal cancer, and 13 lesions were benign. Visual assessment revealed positive 99m Tc-depreotide uptake in 16 of the 21 cancers. The 13 patients without cancer had no depreotide uptake. The Mann-Whitney U test showed a statistically significant difference (P < .005 ) between 99m Tc-depreotide uptake in malignant and benign lesions, for both the 2-hour and the 4-hour measurements. Conclusion . Scintigraphic examination with 99m Tc-depreotide is feasible for imaging esophageal cancer, but the method is not suitable neither for screening or primary diagnosis, because of methods modest sensitivity. Our first results showed high specificity which should be used with caution, as the number of patients was relatively low. Further studies are needed to determine the role of the method.